Використання інструментів онлайн-просування товарів підприємств пивної галузі - Семененко, Катерина Юріївна (My University, 2021)
Дисертаційна робота є комплексним дослідженням теоретичних, методичних та практичних аспектів використання інструментів онлайн-просування підприємствами пивоварної галузі з урахуванням сучасних тенденцій та законодавчих обмежень. Розроблено власну інтерпретацію понять «інтернет-маркетинг» та «онлайн- маркетинг. Обґрунтовано додаткову критеріальну ознаку для класифікації інструментів онлайн-просування – наявність та доступність комунікаційних точок дотику. Досліджено методи сегментування інтернет-користувачів та виокремлено їхні класифікаційні ознаки, розроблено класифікацію інтернет-користувачів залежно від їх виконання ролі в соціальних медіа. Проаналізовано сучасний стан та тенденцій розвитку медіаринку України та встановлено місце інструментів онлайн-маркетингу в структурі медійного ринку з урахуванням існування сегменту Dark market. Виявлено особливості використання інструментів онлайн-просування пива, що ґрунтуються на силі ідеї бренда, виразності комунікації та ступеня диференціації товару. Розроблено універсальний методичний підхід щодо оцінювання ефективності використання онлайн-інструментів просування товарів підприємства. Обґрунтовано необхідність врахування типу інтернет-користувачів залежно профілю споживача та іміджево-цінової сегментації ринку пива при плануванні міксу онлайн-інструментів просування. Розроблено методику визначення ефективної частоти показу комунікаційного повідомлення в мережі Інтернет через інструменти онлайн-просування брендів підприємств пивоварної галузі з урахуванням ринкових чинників. The dissertation is devoted to theoretical and practical principles of the use of on-line-advancement instruments of the enterprises of brewing industry taking into account modern tendencies and legislative limitations in relation to possibilities of beer products advancement. As the result of research, system vision of the use of on-line-advancement instruments based on cooperation of object, methods and object of research is offered. Advantages and lacks of the most widespread authorial determinations interpretation of concepts «internet-marketing», «on-line-marketing» and «on-line advancement instruments of commodities of enterprise» are educed and worked out by the author. An additional criterion feature for classification of on-line-advancement instruments: presence and availability of communication tangencies is proved. The methods of internet-users segmentation and their classification features are distinguished. Authorial classification of internet-users depending on their implementation role in social media is designed. The modern state and trends of media market of Ukraine during the last years is analysed. The place of online-marketing instruments in the structure of media market taking into account the existence of Dark market segment, existence of which conditioned by legislative limitations in relation to the possibilities of alcoholic products advancement, the list and descriptions of instruments of on-line-advancement is set. The methodical approach to the evaluation of the efficiency of the use of online-instruments advancement of commodities of the enterprise, which application will assist the acceptance of reasonable administrative decisions at the development of marketing online-politics principles of the enterprise is designed. Methodical approach is based on successive realization of such stages: preparatory, analytical and administrative is offered. The scientific and methodical approaches to the evaluation of effectiveness level of the use of on-line-advancement instruments of commodities of brewing industry enterprises is worked out. Practical implementation of the use of worked out model is the reference-point in making decision in relation to the conduct of marketing politics of on-line-advancement and achievement of the enterprises’ aims is proved. The universal generally accepted methodology of evaluation the efficiency of the use of online-instruments of commodities’ advancement of the enterprise is worked out. Methodical approach in relation to the evaluation of the efficiency of use of instruments on-line-advancement of commodities of enterprise is offered. The approaches in relation to the use of effective on-line-advancement instruments in social networks are given. The necessity of taking into account the types of Internet-users depending on the role in social Medias at planning of online-instruments of advancement mix is proved. The scientific and methodical approach to the evaluation of effectiveness level of use of on-line-advancement instruments of commodities of brewing industry enterprises is designed. Methodology of the determination of effective frequency show of communication report in the Internet through on-line-advancement instruments of the brands of brewing industry enterprises with taking into account the market factors is worked out.
Keywords: просування; інтернет-маркетинг; цифровий маркетинг; онлайн-маркетинг; інструменти просування; онлайн-просування; соціальні мережі; комунікації; advancement; internet-marketing; digital marketing; on-line-marketing; instruments of advancement; on-line-advancement; social networks; communications